Makna Harta Sebagai Nilai Ekonomi dan Amanah: Analisis Konseptual dalam Akuntansi Syariah - Ulfa Sari; Rohana Rohana; Nur Hikmah; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study explores the meaning of wealth within Islamic accounting by integrating classical and contemporary perspectives to construct a comprehensive conceptual understanding that reflects its economic and moral dimensions. Wealth in Islamic epistemology is positioned not merely as a material asset but as a trust (amanah) that obligates ethical responsibility in its acquisition, management, and distribution. Using a qualitative literature-based approach, this study analyzes authoritative Islamic economic and accounting sources to map the spiritual, social, economic, and accountability values embedded in wealth. The findings reveal that Islamic accounting must extend beyond conventional asset measurement by incorporating dimensions of halal sources, equitable distribution, moral accountability, and societal welfare. Wealth functions not only as an economic instrument but also as a means to uphold justice, prevent inequality, and support public prosperity in accordance with maqasid al-shariah. This conceptual review highlights that the integration of ethical and economic values is essential for strengthening the theoretical foundation of Islamic accounting and ensuring that financial reporting practices remain aligned with the principles of amanah and social responsibility.